2015
DOI: 10.1016/j.jmat.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

An overview of materials issues in resistive random access memory

Abstract: Resistive random access memory (RRAM) is a very promising next generation non-volatile RAM, with quite significant advantages over the widely used silicon-based Flash memories. For RRAM, material with switchable resistance, working as the storage medium, is the most important part for the performance of the memory. In this review, as a start, some general hints for the materials selection are proposed. Then most recent studies on this emerging memory from the perspective of materials science are summarized: va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 84 publications
2
72
0
2
Order By: Relevance
“…Finally, the presence of the broad and weak feature f in the O K absorption spectrum of the TiO 2 film grown on the deg-Si is an evidence of signs of ordered structure of the anatase type in this film. [40] In view of the electrophysical studies mentioned above, one can conclude the correlation exists between the crystallinity of the film structure and resistances and switching voltages stability that agrees well with [29–32]. …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Finally, the presence of the broad and weak feature f in the O K absorption spectrum of the TiO 2 film grown on the deg-Si is an evidence of signs of ordered structure of the anatase type in this film. [40] In view of the electrophysical studies mentioned above, one can conclude the correlation exists between the crystallinity of the film structure and resistances and switching voltages stability that agrees well with [29–32]. …”
Section: Resultssupporting
confidence: 73%
“…One of the factors affecting the stability of the resistive switching is a microstructure of the active layer. [29–31] In these references it was found that with increase of crystallinity (decrease of grain boundary density), the resistances and switching voltages become much more stable. According to [32], the location and growth direction of the filaments are confined by the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of bipolar switching (illustrated in Figure b), the SET and RESET states are controlled by reverse polarities. The change of resistance in filamentary RRAM occurs by creation and rupture of conductive filaments in the dielectric, while, for the nonfilamentary devices, other physical mechanisms, such as charge trapping and de‐trapping and redistribution of oxygen vacancies (caused by electronic transport properties of the tunnel barrier), account for the resistance change . Therefore, 4 main types of RRAM are identified as follows: Electrochemical metallization bridge ReRAM (CBRAM) Metal oxide‐bipolar filamentary ReRAM, valence change memory (VCM) Metal oxide‐unipolar filamentary ReRAM Metal oxide‐bipolar nonfilamentary ReRAM …”
Section: Principles Of Envmsmentioning
confidence: 99%
“…Phase change materials (PCMs) are a special group of chalcogenides with a peculiar combination of physical properties that have a variety of important applications in non-volatile electronic, optical and photonic data storage devices [18,19,20,21,22,23], memristors and processors [24,25,26,27,28], spintronics [29,30,31,32,33], display and data visualization applications [34], and so on. PCMs can undergo rapid and reversible phase transitions between an amorphous and a crystalline phase upon heating.…”
Section: Introductionmentioning
confidence: 99%